2003
DOI: 10.1038/sj.gene.6363970
|View full text |Cite
|
Sign up to set email alerts
|

Murine serine proteases MASP-1 and MASP-3, components of the lectin pathway activation complex of complement, are encoded by a single structural gene

Abstract: Activation of the lectin pathway of complement is initiated by the binding to microbial carbohydrate structures of a multimolecular fluid-phase complex composed of a carbohydrate recognition subcomponent that associates with three specific serine proteases and an enzymatically inert protein of 19 kDa. The first carbohydrate recognition subcomponent of the lectin pathway identified was mannan-binding lectin (MBL), hence the serine proteases were named MBL-associated serine proteases (MASPs) and numbered accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
1
7
1
Order By: Relevance
“…This is in contrast to what was seen in mammals, where both MASP-3 and MASP-1 mRNA transcripts were detected (Fig. 7, upper last lane) (20). Analyzing liver mRNA from other birds (including turkey, duck, goose, ostrich, and pigeon) on Northern blots suggested that the absence of MASP-1 may be a general phenomenon in birds (Fig.…”
Section: Expression Of the Lectin Pathway Componentscontrasting
confidence: 48%
See 3 more Smart Citations
“…This is in contrast to what was seen in mammals, where both MASP-3 and MASP-1 mRNA transcripts were detected (Fig. 7, upper last lane) (20). Analyzing liver mRNA from other birds (including turkey, duck, goose, ostrich, and pigeon) on Northern blots suggested that the absence of MASP-1 may be a general phenomenon in birds (Fig.…”
Section: Expression Of the Lectin Pathway Componentscontrasting
confidence: 48%
“…4 and 6) (N. J. Lynch, unpublished observations). In contrast, the messages for MASP-1, MASP-2, and MAp19 mRNA are restricted to the liver in all species investigated to date, and those for MBL and the plasma ficolins are mainly expressed in the liver (2,20,24,45). The conservation of MASP-3 and its unique expression pattern suggest that its function may be decidedly different from those of the other lectin pathway components.…”
Section: Figurementioning
confidence: 71%
See 2 more Smart Citations
“…Murine MASP-1 (18) and MASP-2 (19) have already been cloned and characterized. We previously described murine MASP3 cDNA from the livers of C57BL/6J mice (20). In the present study, we generated MASP-1 and MASP-3 doubledeficient mice using a standard gene targeting method.…”
mentioning
confidence: 99%